Politics Representation and Symbolic Violence through the Discourse of Seram as Nusa Ina - Flavius Floris Andries (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
Political representation and symbolic violence through discourse Seram as Nusa Ina (Mother Island) are interesting phenomenon to be studied. This research was conducted with a qualitative method by in-depth interview and participation observation which aims to know how does this discourse view. The cultural study was applied in order to comprehend the manners of creating, producing, and disseminating the meanings from the perspective of non-Seram society and what their views on the discourse in understanding Moluccas universal identity. The process of data analysis by using the cultural studies approach generated the findings i.e the Nunusaku myth that legitimizes and strengthens Seram as Nusa Ina in society, and that there was a significant influence of myth and discourse in Moluccas identity formation universally in the form of folk songs or reliefs that always shade of Seram in represents the Moluccans. The discourse of Seram as Nusa Ina for the community of non-Seram, especially for Southeast people, is not substantial because they do not have emotional connection or relationship with the genealogy and cultural discourse. They have the other myth and the other own discourse about the myth itself such as Vernusang Island which was sinking in the formation of people’s live in the Southeast. Therefore, the discourse of Seram as Nusa Ina which is forced to become a part of the discourse of Southeast People is a form of a false consciousness as well as form of political representation and symbolic violence.